Energy, exergy and economic evaluation comparison of small-scale single and dual pressure organic Rankine cycles integrated with low-grade heat sources (2017)
Low-grade heat sources such as solar thermal, geothermal, exhaust gases and industrial waste heat are suitable alternatives for power generation which can be exploited by means of small-scale Organic Rankine Cycle (ORC). This paper combines thermodynamic optimization and economic analysis to assess the performance of single and dual pressure ORC operating with different organic fluids and targeting small-scale applications. Maximum power output is lower than 45 KW while the temperature of the heat source varies in the range 100-200 °C. The studied working fluids, namely R1234yf, R1234ze(E) and R1234ze(Z), are selected based on environmental, safety and thermal performance criteria. Levelized Cost of Electricity (LCOE) and Specific Investment Cost (SIC) for two operation conditions are presented: maximum power output and maximum thermal efficiency. Results showed that R1234ze(Z) achieves the highest net power output (up to 44 kW) when net power output is optimized. Regenerative ORC achieves the highest performance when thermal efficiency is optimized (up to 18%). Simple ORC is the most cost-effective among the studied cycle configurations, requiring a selling price of energy of 0.3 USD/kWh to obtain a payback period of 8 years. According to SIC results, the working fluid R1234ze(Z) exhibits great potential for simple ORC when compared to conventional R245fa.